On Strongly Regular Graphs With m_2 = qm_3 AND m_3 = qm_2 for q = 5,6,7,8 - Lepović, Mirko (Sarajevo Journal of Mathematics, 2020)
We say that a regular graph G of order n and degree r1 (which is not the complete graph) is strongly regular if there exist non-negative integers τ and θ such that |S_iS_j| = τ for any two adjacent vertices i and j, and |S_iS_j| = θ for any two distinct non-adjacent vertices i and j, where S_k denotes the neighborhood of the vertex k. Let λ_1 = r, λ_2 and λ_3 be the distinct eigenvalues of a connected strongly regular graph. Let m_1 = 1, m_2 and m_3 denote the multiplicity of r, λ_2 and λ_3, respectively. We describe the parameters n, r, τ and θ for strongly regular graphs with m_2 = qm_3 and m_3 = qm_2 for q = 5,6,7,8.